Green Taxonomy Role As Green Bonds Standardized Policy Instrument - Suci Ariyanti; Andy Usmina Wijaya; Sekaring Ayumeida Kusnadi (Fakultas Hukum Universitas Islam Malang, 2023)
The increasing environmental problems and the steps taken to solve them are becoming a very important topic in today's society. With this in mind, the Financial Services Authority as one of the regulators in the field of investment issues a green taxonomy as a classification and qualification process for dividing sectors of sustainable economic activity. Relevance of the issuance of green taxonomy with the expected goals and can motivate the growth of green bonds as an alternative investment in sustainable and environmentally sound economic development. This research aims to increase the relevance of this matter. This research was conducted using normative touristic research using a statutory approach. From the research results it was found that Indonesia's green taxonomy 1.0 is an instrument that has relevance to the sustainable finance roadmap phase I (2015-2019) - phase II (2021-2025) and is expected to be the first step in developing the next regulation.